Knowledge, attitude, and practice toward advanced precision radiotherapy among patients with head and neck cancer - Zhanfei Guo; Zhanfei Guo; Qingrui Cai; Bingbing Liu; Liufang Zhao; Yanyan Xie; Zhijia Li; Rui Liu; Yunxiao Wang; Xiaodan Chen; Zhiwei Zhang; Zhiwei Zhang (Frontiers Media S.A., 2024)
BackgroundAdvancements in radiotherapy (RT) technology have led to the prominence of precision RT in head and neck cancer (HNC) treatment. The new progress in precision RT offers more efficient therapy, potentially improving outcomes for HNC patients.ObjectiveThe present cross-sectional study aimed to assess the knowledge, attitude, and practice (KAP) of patients in advanced precision RT for HNC treatment.MethodsThis study enrolled HNC patients at the Affiliated Hospital of Hebei University of Engineering between October 2023 and May 2024. Then, the demographic data and KAP scores were collected using an investigator-designed questionnaire. Afterwards, descriptive statistics were provided for all study variables, and the relationship among KAP was analyzed using appropriate statistical tests, including Spearman correlation, logistic regression, and path analysis.ResultsA total of 436 participants with a mean age of 52.03 ± 12.19 years old were included. The mean knowledge score, attitude score, and practice score were 18.33 ± 4.21, 36.14 ± 1.71, and 26.26 ± 1.83, respectively. Although most of the participants were unfamiliar with advanced precision RT, they expressed a high willingness to follow their doctor's recommendation for this treatment. The multivariable analysis revealed a positive association between attitude score and proactive practice. The path analysis revealed that knowledge directly influenced attitude and practice, while attitude directly impacted practice.ConclusionHNC participants had poor knowledge of advanced precision RT techniques, but had a positive attitude and the willingness to undergo treatment when recommended by their physicians. These results suggest that improving patients' awareness for advanced precision RT can help to promote better attitude and advanced precision RT practice.